2011
DOI: 10.1037/a0022105
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-based motion categorization by pigeons.

Abstract: To examine if animals could learn action-like categorizations in a manner similar to noun-based categories, eight pigeons were trained to categorize rates of object motion. Testing 40 different objects in a go/no-go discrimination, pigeons were first trained to discriminate between fast and slow rates of object rotation around their central y-axis. They easily learned this velocity discrimination and transferred it to novel objects and rates. This discrimination also transferred to novel types of motions inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
17
2
Order By: Relevance
“…Unlike Cook et al (2011) who reported a reliable discrimination after as little as six training sessions (or 480 trials), we have observed no noticeable learning across two weeks of training (a total of 1,680 trials). Importantly, the rotational difference between our stimuli, and therefore their discriminability, was comparable to that in Cook et al's (2011) study.…”
Section: Resultscontrasting
confidence: 97%
See 4 more Smart Citations
“…Unlike Cook et al (2011) who reported a reliable discrimination after as little as six training sessions (or 480 trials), we have observed no noticeable learning across two weeks of training (a total of 1,680 trials). Importantly, the rotational difference between our stimuli, and therefore their discriminability, was comparable to that in Cook et al's (2011) study.…”
Section: Resultscontrasting
confidence: 97%
“…In Experiment 3, we found that pigeons appeared to be more sensitive to the differences in size than to the differences in speed in a two-alternative forced-choice task; the same was true for human participants (cf Figure 4). Overall, our results are not consistent with many earlier reports of motion discrimination in pigeons that suggested high sensitivity to object speed (Cook et al, 2011;Herbranson et al, 2002;Koban & Cook, 2009; but see Hodos, Smith, & Bonbright, 1976;Mulvanny, 1978). Importantly, the magnitude of the differences among the stimuli in our study was comparable to the previously used magnitudes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations